2013
DOI: 10.1097/01.med.0000433071.11466.7f
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenic obesity

Abstract: Purpose of review The increasing prevalence of sarcopenic obesity in older adults has heightened interest in identifying the most effective treatment. This review highlights recent progress in management with an emphasis on lifestyle interventions and pharmacologic therapy aimed at reversing sarcopenic obesity. Recent findings While weight loss and exercise independently reverse sarcopenic obesity, they act synergistically in combination to improve body composition and physical function beyond which is obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(79 citation statements)
references
References 83 publications
3
72
0
4
Order By: Relevance
“…It is possible that exercise programs associated with lifestyle interventions have more beneficial effects on physical function of older people with SO. Evidence in the literature indicates that a combination of diet-induced weight loss and physical exercise produces the best results for body composition in older people with obesity or SO 10 , 28 . This combination helps to preserve muscle mass during the process of weight loss and to improve physical function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that exercise programs associated with lifestyle interventions have more beneficial effects on physical function of older people with SO. Evidence in the literature indicates that a combination of diet-induced weight loss and physical exercise produces the best results for body composition in older people with obesity or SO 10 , 28 . This combination helps to preserve muscle mass during the process of weight loss and to improve physical function.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis study concluded that power training with high-speed resistance exercises might be more beneficial to older people than traditional strength training 9 . Resistance exercises have also been recommended as a non-pharmacological therapy for older people with SO to minimize sarcopenia and ameliorate the pro-inflammatory state associated with obesity 10 . Nonetheless, the potential effects of resistance exercises on the physical function of older people with SO are poorly documented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, exercise combined with amino acid supplementation was most effective in improving muscle mass, strength and walking speed in women with sarcopenia [64]. Another strategy besides exercise and diet could include a pharmaceutical approach such as hormone therapy (growth hormone), since low levels of growth hormone are a risk factor for sarcopenia [65]. SO is a continuous process for years and decades, although it progresses and accelerates faster after the age of 60.…”
Section: Assessment and Definition Of Sarcopenic Obesitymentioning
confidence: 99%
“…This will prove to be a huge burden for the health care system, not because of obesity itself but because of the associated complications such as coronary heart disease, stroke, type 2 diabetes mellitus (T2D), cancers, and physical disability. In addition, obesity in older adults increases the risk of institutionalization and mortality [3]. The surge in obesity can be attributed to the changes in lifestyle, for instance, wide availability of high calorie food and decreased physical activity.…”
Section: Introductionmentioning
confidence: 99%